Women’s household decision-making power and contraceptive use in Mali - Seidu, Abdul-Aziz; Ahinkorah, Bright O.; Armah-Ansah, Ebenezer K.; Dadzie, Louis K.; Aboagye, Richard G.; Ameyaw, Edward K.; Budu, Eugene; Zegeye, Betregiorgis; Yaya, Sanni (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background Utilization of contraceptives remains low in several countries in sub-Saharan Africa despite evidence of its benefits. Several factors are associated with contraceptive use. However, little is known about the association between women’s decision-making capacity and the utilization of contraceptives in Mali. This study sought to determine the effect of women’s household decision-making power on contraceptive use in Mali. Methods This study involved a cross-sectional analysis of data from the 2018 Mali Demographic and Health Survey. A total of 7893 married women were included in the final analysis. A binary logistic regression analysis was conducted with statistical significance set at p < 0.05. Results Contraceptive use among married women in Mali was 17.1%. The odds of using contraceptives were higher among women with joint decision-making with their husbands on how to spend respondent’s earnings [aOR = 1.79; 95% CI = 1.12, 2.85], joint decision-making with their husbands on what to do with their husband’s earnings [aOR = 1.43; 95% CI = 1.12, 1.83], and joint decision-making with husband on large household purchases [aOR = 1.32; 95% CI = 1.10, 1.59]. Deciding alone on a visit to family or relatives was associated with lower odds of contraceptive use [AOR = 0.72; 95% CI = 0.58, 0.89]. Conclusion The study has revealed that joint household decision-making is positively associated with contraceptive use. Therefore, to achieve Sustainable Development Goal 3, the ministry for the advancement of women, children and families and related stakeholders must unearth strategies to empower women in joint decision-making and encourage men’s involvement in contraceptive decision-making.